2011
DOI: 10.1039/c0cp01688h
|View full text |Cite
|
Sign up to set email alerts
|

New nanostructured heterogeneous catalysts with increased selectivity and stability

Abstract: In this perspective, several examples of work from our laboratory are reported where colloidal or self-assembly chemistry has been used to design new catalysts with specific properties. In the first, platinum nanoparticles with well-defined shapes have been dispersed on a high-surface-area silica support in order to take advantage of the structure sensitivity exhibited by the interconversion between the cis and trans isomers of olefins. The second case involves the use of dendrimers as scaffolding structures t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
92
0
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 110 publications
(97 citation statements)
references
References 55 publications
2
92
0
3
Order By: Relevance
“…They found that the thermoresponsive PNIPA shell with limited cross-linking allows for particularly efficient control of the catalysis of encapsulated Au nanoparticles. [13] Recently, yolk-shell structures that consist of a single metal nanoparticle within an inorganic [14][15][16][17] or polymeric shell [18,19] have become the subject of intense research. These systems can be used to tune the catalytic activity of the enclosed nanoparticle by a suitable architecture of the shell.…”
mentioning
confidence: 99%
“…They found that the thermoresponsive PNIPA shell with limited cross-linking allows for particularly efficient control of the catalysis of encapsulated Au nanoparticles. [13] Recently, yolk-shell structures that consist of a single metal nanoparticle within an inorganic [14][15][16][17] or polymeric shell [18,19] have become the subject of intense research. These systems can be used to tune the catalytic activity of the enclosed nanoparticle by a suitable architecture of the shell.…”
mentioning
confidence: 99%
“…Mesoporous silica is an ideal support material for the preparation of highly active catalysts because of its high surface area, inert nature of silica, and functionalization ability [1][2][3][4][5][6][7][8][9][10]. Among various approaches to functionalizing mesoporous silica, silane-coupling reaction, a reaction between surface silanol and functional molecules containing a trialkoxy group, is one of the most common procedures for the preparation of a supported catalyst.…”
Section: Introductionmentioning
confidence: 99%
“…[45] More research effort could be devoted to defect engineering in the design of novel catalysts. [46] Taken together, our studies demonstrate control on the production of unique nanostructures and structure-enhanced properties, which is the focal point of designing nanomaterials for various applications. .…”
Section: Methodsmentioning
confidence: 94%